2020
DOI: 10.1111/and.13795
|View full text |Cite
|
Sign up to set email alerts
|

Impact of silymarin on cadmium‐induced apoptosis in human spermatozoa

Abstract: Oxidative stress‐induced apoptosis in spermatozoa may lead to male infertility. Environmental pollutants and heavy metals such as cadmium cause harmful effects on the reproductive system and sperm parameters through the induction of oxidative stress. Silymarin, as a potent antioxidant, is able to inhibit oxidative stress. This study was performed to investigate the protective effects of silymarin on cadmium‐induced toxicity in human spermatozoa. Sperm samples were divided into the following five groups: (a) sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…This induces apoptosis by releasing apoptogenic factors such as cytochrome c and apoptosis-inducing factors (AIF) from the mitochondria (Ott et al, 2007). Accordingly, in the previous study, we showed that cadmium could trigger apoptosis in human spermatozoa (Etemadi et al, 2020). Cadmium-induced oxidative stress may also be a hypothesis for affecting the plasma membrane integrity and early induction of the acrosomal reaction in the spermatozoa.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This induces apoptosis by releasing apoptogenic factors such as cytochrome c and apoptosis-inducing factors (AIF) from the mitochondria (Ott et al, 2007). Accordingly, in the previous study, we showed that cadmium could trigger apoptosis in human spermatozoa (Etemadi et al, 2020). Cadmium-induced oxidative stress may also be a hypothesis for affecting the plasma membrane integrity and early induction of the acrosomal reaction in the spermatozoa.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, silymarin reduced the increased amount of malondialdehyde in varicocele rats (Moshtaghion et al, 2013). Furthermore, the protective effects of silymarin have proven on some human sperm parameters (Aghashahi et al, 2020; Etemadi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…An important factor in the transmission of species from generation to generation is the selection of superior cellular traits and the rejection of cellular mechanisms that are detrimental to reproductive development. Various physical factors, toxins, radioactivity, etc., have the chance to stimulate the activation of this mechanism (Alam et al, 2010;Etemadi et al, 2020;Wang et al, 2017;Xue et al, 2022). If spermatogenesis is compromised in any way, germ cells often go into apoptosis by default (Lin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Spermatozoa treated with Cd resulted in chromatin condensation; DNA fragmentation and matrix metalloproteinases (MMPs) damage which are typical morphologic and biochemical features of apoptosis were reported by Etemadi et al (2020). From these studies, Cd can directly induce toxicity on matured sperm cells, thus, mitigating its fertilising capacity.…”
Section: Spermatozoamentioning
confidence: 98%
“…The seminiferous tubule germ cells have been reported to respond to different imminent testicular toxicants by apoptosis (Blanchard & Johnson, 1997). Several studies have reported Cd‐induced testicular apoptosis and their mechanism of action (Amanpour et al, 2020; Bashir et al, 2019; Boujelben et al, 2018; Dai et al, 2019; Etemadi et al, 2020; Saha et al, 2019; Shi & Fu, 2019; Xu & Yang, 2018) see Figure 2.…”
Section: Introductionmentioning
confidence: 99%